53 Improving Door to Needle Times in Acute Stroke. (16th September 2019) - Khalil, Dzulkarnain; Connaughton, Fiona; Carolan, Danielle; Sirbu, Mihaela; Lynch, Bernadette; Daries, Juanine; Sullivan, Patrick; Stringer, Tony; Carter, Shane; Fleming, Thomas; Kelly, Conor; Basit, Mian; et al.
Abstract: Background: During an acute stroke, 2 million neurons are lost every minute. When compared with aging, 2 million neurons are lost every 22 days. Prompt reperfusion of an acute stroke, in the form of intravenous thrombolysis (IV tPA) or intraarterial thrombectomy (IAT) would save these neurons and result in saving significant disability. We endeavoured as part of a quality improvement (QI) project to improve our times. Methods: A local QI steering group was formed which comprised of representatives from the stroke team, radiology, emergency, laboratory, telephone and clerical departments. We outlined our stroke pathway from when the patient arrives to when the patient received IVtPA or IAT. Data was collected prospectively and retrospectively from real time, chart reviews, radiology Picture Archiving Communication System (PACS) and Hospital Inpatient Patient Enquiry (HIPE) stroke data system. We recorded times from door to computed tomography (CT), CT to issue of report and CT report to IVtpA or IAT. The data was reviewed to ascertain if there were any delays at each stage of the pathway. Results: There were steps in the pathway that were non-variable and those that were highly variable. In general, steps from door to CT, were consistent each time. In contrast, steps from CT completion to IVtPA or IAT, was highly variable dependent on a patient's clinical condition and decision making expertise available. We addressed duplication of tasks and additional non-urgent investigations. The presence of the stroke team for IVtPA and IAT made decision making faster. The overall median door to CT time reduced by 9 minutes, from 22 to 13 minutes. The overall median door to IVtPA time decreased by 24 minutes, from 83 to 59 minutes. Our hospital had the fastest door to CT time for IAT patients in 2018 nationally. Conclusion: Delays in the stroke pathway were rectifiable by change of practice. Most changes were simple without need of any additional resource.